The term structure of bond market liquidity conditional on the economic environment: An analysis of government guaranteed bonds - Philipp Schuster; Marliese Uhrig-Homburg (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2012)
We analyze the term structure of illiquidity premiums as the difference between the yield curves of two major bond segments that are both government guaranteed but differ in their liquidity. We show that its characteristics strongly depend on the economic situation. In crisis times, illiquidity premiums are higher with the largest increase for short-term maturities. Moreover, their reaction to changes in fundamentals is only significant during crises: premiums of all maturities depend on inventory risk, short maturities are highly sensitive to liquidity preferences (flight-to-liquidity). Therefore, calibrating risk management models in normal times underestimates illiquidity risk and misjudges term structure effects.
urn:nbn:de:swb:90-309642
Keywords: G01; G11; G12; G13; 330; bond liquidity; term structure of illiquidity premiums; regime-switching; financial crisis; flight-to-liquidity; Zinsstruktur; Rentenmarkt; Marktliquidität; Liquiditätspräferenz; Finanzmarktkrise; Theorie; Schätzung; Öffentliche Anleihe; Deutschland